Spinal cord stimulation of the conus medullaris for refractory pudendal neuralgia: A prospective study of 27 consecutive cases. Issue 2 (19th November 2013) - Buffenoir, Kevin; Rioult, Bruno; Hamel, Olivier; Labat, Jean‐Jacques; Riant, Thibault; Robert, Roger
<x xml:space="preserve">Abstract</x> Aims Thirty percent of patients with pudendal neuralgia due to pudendal nerve entrapment obtain little or no relief from nerve decompression surgery. The objective was to describe the efficacy of spinal cord stimulation of the conus medullaris in patients with refractory pudendal neuralgia. Methods This prospective study, conducted by two centers in the same university city, described the results obtained on perineal pain and functional disability in all patients with an implanted conus medullaris stimulation electrode for the treatment of refractory pudendal neuralgia. Twenty‐seven consecutive patients were included by a multidisciplinary pelvis and perineal pain clinic between May 2011 and July 2012. Mean follow‐up was 15 months. The intervention was an insertion of a stimulation electrode was followed by a test period (lasting an average of 13 days) before deciding on permanent electrode implantation. Maximum and average perineal pain scores and the pain‐free sitting time were initially compared during the test and in the long‐term (paired t‐test). The estimated percent improvement (EPI) was evaluated in the long‐term. Results Twenty of the 27 patients were considered to be responders to spinal cord stimulation and 100% of implanted patients remained long‐term responders (mean tripling of sitting time, and mean EPI of 55.5%). Conclusions Spinal cord stimulation of the conus medullaris is a safe and effective technique for long‐term treatment of refractory pudendal neuralgia. Routine use of this technique, which has never been previously reported in the literature in this type of patient, must now be validated by a larger scale study. Neurourol. Urodynam. 34:177–182, 2015. © 2013 Wiley Periodicals, Inc.